2013
DOI: 10.5152/akd.2013.234
|View full text |Cite
|
Sign up to set email alerts
|

Gender specific association of ABCA1 gene R219K variant in coronary disease risk through interactions with serum triglyceride elevation in Turkish adults

Abstract: Objective: ATP binding cassette transporter A1 (ABCA1) controls the reverse cholesterol transport. Some ABCA1 variants are correlated with serum high-density lipoprotein cholesterol (HDL-C) and other lipid concentrations. We aimed to explore the relationship of ABCA1 gene with both the lipid profile and coronary heart disease (CHD) risk. Methods: Selected 627 individuals of the Turkish Adult Risk Factor Study were genotyped for ABCA1 R219K polymorphism using PCR-RFLP (polymerase chain reaction-restriction frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
(52 reference statements)
4
19
0
Order By: Relevance
“…Consistent with our results, Villard et al reported R219K SNP to be associated with a significant modification of cholesterol efflux capacity in a sex-dependent manner [53]. Genderspecific differential effect of ABCA1 gene polymorphisms was also observed in coronary disease risk and plasma lipid levels in Turkish adults [54]. These observations could be explained by the fact that sex hormones regulate many genes involved in HDL biogenesis, leading to altered lipid levels in women compared with men [53].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our results, Villard et al reported R219K SNP to be associated with a significant modification of cholesterol efflux capacity in a sex-dependent manner [53]. Genderspecific differential effect of ABCA1 gene polymorphisms was also observed in coronary disease risk and plasma lipid levels in Turkish adults [54]. These observations could be explained by the fact that sex hormones regulate many genes involved in HDL biogenesis, leading to altered lipid levels in women compared with men [53].…”
Section: Discussionsupporting
confidence: 91%
“…In healthy-weight subjects, R219K SNP was shown to be associated with altered HDL-c phenotype [65,66]. Homozygotes of the A allele of R219K were associated with increased LDL-C and TC and decreased HDL-c concentrations in Turkish population [54]. Similarly, young Greek women with the GG genotype of the same SNP exhibited lower TC and LDL-c levels compared with the GA genotype [22].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the increased serum levels of LDL cholesterol were observed in the NAFLD patients with the ABCA1 rs2066714 C allele. The same result was also reported in Turkish adults indicating that the R219K variant (rs2230806 G > A) of ABCA1 was associated with the increased serum LDL cholesterol levels (37). No significant difference in the serum LDL cholesterol levels of NAFLD patients was observed between the carriers and noncarriers of the ABCA1 rs1800977 A, rs2066715 C, and rs2230808 T.…”
Section: Discussionsupporting
confidence: 82%
“…We examined the impact of the R219K , R1587K and I883M of ABCA1 polymorphisms as a genetic influence on the lipid profile in Greek subjects. In this context, the possible effects of the ABCA1 polymorphisms on lipids or cardiovascular disease were recently evaluated in various populations such as Japanese [ 11 ] in which correlation with HDL-C concentrations was found, Saudi [ 12 ] in which the ABCA1 C69T gene frequency was higher in healthy subjects compared with diabetic patients, Chinese [ 13 ], in which ABCA1 gene R219K polymorphism was associated with ischemic stroke, Greek [ 5 - 7 ] in which a gender-specific effect of the R219K polymorphism on plasma lipids was demonstrated, Turkish [ 14 ] in which a gender-specific effect of the R219K polymorphism on plasma lipids and CHD was shown and Mexican [ 15 ] in which several European loci as well as a novel one for high TG and low HDL-C levels were identified. However, the results are still confusing.…”
Section: Discussionmentioning
confidence: 99%